The body on the train : a Kate Shackleton mystery - Brody, Frances (Brody, Frances. Kate Shackleton mystery., 2021)
Investigating the discovery of a body on a train in 1929 Yorkshire, Kate Shackleton finds her efforts complicated by regional coalfield politics, a suspicious death, and a wrongful arrest.